Bridging the gap between the agriculture and health sectors - von Braun, Joachim; Ruel, Marie T.; Gillespie, Stuart (International Food Policy Research Institute, 2011)
As a unified set of global poverty reduction goals, the Millennium Development Goals (MDGs) in principle provide an opportunity for overcoming sectoral divides and forging effective links between agriculture and health. Both agriculture and health are important for most of the MDGs, and positive synergies could link agricultural and health policy, programming, and research in ways that would benefit both sectors and advance the MDGs as a whole. But these links have not materialized in satisfactory ways.